2017
DOI: 10.1108/jmp-07-2016-0223
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness as substitute for transformational leadership

Abstract: Purpose Transformational leaders spark the intrinsic motivation of employees, thereby stimulating their extra-role performance. However, not all employees are lucky enough to have a transformational leader. The purpose of this paper is to investigate to what extent mindfulness can function as a substitute for transformational leadership. By being attentive to and aware of what is taking place in the present, mindfulness provides employees with a source of intrinsic motivation that lies within the person, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 68 publications
(135 reference statements)
3
45
0
5
Order By: Relevance
“…Furthermore, other mindful leadership studies reveal that continuous mindfulness practices in leadership reduces stress, increases health, and can affect transformational leadership. Therefore, it increases intrinsic motivation and performance (Kroon, Van Woerkom, & Menting, 2017;Wasylkiw, Holton, Azar, & Cook, 2015). When leaders consider ways that can increase effectivity and also reduce their stress, mindfulness can offer practices for both.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other mindful leadership studies reveal that continuous mindfulness practices in leadership reduces stress, increases health, and can affect transformational leadership. Therefore, it increases intrinsic motivation and performance (Kroon, Van Woerkom, & Menting, 2017;Wasylkiw, Holton, Azar, & Cook, 2015). When leaders consider ways that can increase effectivity and also reduce their stress, mindfulness can offer practices for both.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we employed bootstrapped mediation analysis (Hayes, 2018), a contemporary and robust technique that has become quite widely used in recent years (e.g. Bentein, Guerrero, Jourdain and Chênevert, 2017;Kroon, van Woerkom and Menting, 2017). The bootstrapped mediation analyses (50,000 samples)…”
Section: Results and Analysismentioning
confidence: 99%
“…Second, mindfulness corresponds to living in the moment (Sethi, 2009), while EI emphasizes the need to accurately understand emotions (Salovey & Mayer, 1997); given that emotions occur in the moment, assessing them accurately as they occur is an important aspect of mindfulness. Third, the pursuit of emotional and intellectual growth is at the centre of EI (Salovey & Mayer, 1997), while mindfulness emphasizes the importance of rigorous mental practice (Kroon et al, 2017). Said another way, how can emotional and intellectual growth come about without rigorous mental practice?…”
Section: Ei and Mindfulnessmentioning
confidence: 99%
“…When drawing connections between EI and mindfulness, it also is helpful to consider how Goleman's (2004) five components of EI-motivation, self-awareness, self-regulation, empathy, and social skills-can be developed through mindfulness. For example, Brown and Ryan (2003) and Levesque and Brown (2007) found that individuals who are mindful are more intrinsically motivated (as cited in Kroon et al, 2017). Brown and Ryan (2003) also point out that those who are mindful have greater self-awareness and are better able to regulate their behaviour (as cited in Kroon et al, 2017).…”
Section: Ei and Mindfulnessmentioning
confidence: 99%